Justice Sensitivity in Middle Childhood: Measurement and Location in the Temperamental and Social Skills Space. Issue 4 (4th July 2021) - Strauß, Sophie; Bondü, Rebecca; Roth, Felix
Abstract: Research suggested that justice sensitivity (JS)—the tendency to perceive and negatively respond to injustice—may already manifest in middle childhood, but empirical evidence is sparse. We, therefore, examined the measurement of JS in this age range and its associations with prosocial behavior, aggressive behavior, temperamental traits, and social skills. We had 361 children between 6 and 10 years of age and/or their parents rate the children's JS and its potential correlates. We replicated the JS-factor structure with three correlated subscales in both child and parent-ratings that showed strict measurement invariance. In line with previous findings in older age groups, victim JS positively predicted aggressive and negatively predicted prosocial behavior, whereas observer and perpetrator JS positively predicted prosocial and perpetrator JS negatively predicted aggressive behavior. The JS perspectives showed expected links with temperamental traits. All three subscales were positively related to empathy and theory of mind, but victim JS was negatively related to affective self-regulation. Findings suggest that interpersonal differences in JS may reliably and validly be measured in middle childhood and that JS is associated with aggressive and prosocial behavior already in childhood. Thus, future research should consider the role of JS for moral and personality development and developmental psychopathology.